2017
DOI: 10.7888/juoeh.39.187
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Specific Risk Mitigation Techniques Used in the Production and Handling of Manufactured Nanomaterials: A Systematic Review

Abstract: : Many kinds of manufactured nanomaterials (MNMs) have been developed and used as basic materials of industrial products, and they may pose health risks for workers in not only developed countries but also in developing countries. Few studies have looked at the evidence for effects of controls that mitigate the risk of exposure to MNMs. Therefore, we systematically searched the literature from the year 2000 to 2015. We included studies that compared the use of an exposure control to the situation without such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…A recent review that quantified the efficiency of PPE and engineering controls (Goede et al, 2018), especially for engineered NPs in controlled scenarios such as laboratories, reported that the available data are inconclusive. Previous studies discussed the efficiency of PPE such as protective gloves, clothes, filtering facepieces respirators and half mask respirators (Kim et al, 2006(Kim et al, , 2007Lee et al, 2007;Myojo et al, 2017;Tsai et al, 2010). A review of this literature, based on search terms "nanoparticles", "protective equipment" "ventilation", "extraction"," safety", "mitigation", evidenced that: (i) studies for incidentally-released NPs are less frequent than for engineered ones; (ii) in spite of a great number of studies on PPE efficiency, less information can be found about the effectiveness of applied technical measures, and they refer mostly to laboratory-scale; (iii) the results obtained cannot be easily generalized beyond the specific cases; and (iv) experimental studies at industrial scale constitute a clear research gap.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review that quantified the efficiency of PPE and engineering controls (Goede et al, 2018), especially for engineered NPs in controlled scenarios such as laboratories, reported that the available data are inconclusive. Previous studies discussed the efficiency of PPE such as protective gloves, clothes, filtering facepieces respirators and half mask respirators (Kim et al, 2006(Kim et al, , 2007Lee et al, 2007;Myojo et al, 2017;Tsai et al, 2010). A review of this literature, based on search terms "nanoparticles", "protective equipment" "ventilation", "extraction"," safety", "mitigation", evidenced that: (i) studies for incidentally-released NPs are less frequent than for engineered ones; (ii) in spite of a great number of studies on PPE efficiency, less information can be found about the effectiveness of applied technical measures, and they refer mostly to laboratory-scale; (iii) the results obtained cannot be easily generalized beyond the specific cases; and (iv) experimental studies at industrial scale constitute a clear research gap.…”
Section: Introductionmentioning
confidence: 99%
“…During the years working with nanomaterials, various organizations and research groups have constantly been evaluating whether the quality of the masks is effective in controlling access to the organism [580][581][582]. Nowadays, it is possible to access the comparison of specific nomenclatures and selection criteria available for different international organizations [579,[583][584][585][586]. There is even a new trend for creating nanostructured face masks for obtaining nanofibers that can incorporate multifunctional nanomaterials, which consist of polymeric nanofibers fabricated by electrospinning, phase separation, template synthesis, or self-assembly techniques, which include different nanoparticles such as metals (gold, silver, Zn), metal oxide (TiO 2 ), metal composites (CuO-polyacrylonitrile), graphene, or carbon nanotubes [587].…”
Section: Respiratory Protective Masksmentioning
confidence: 99%